PENYULUHAN PEMILAHAN DAN PENGELOLAAN SAMPAH RUMAH TANGGA PLASTIK DENGAN METODE 3R DI SMK N 7 BANDAR LAMPUNG - Rohiman, Rohiman; Yusuf, Andi Wahyu Zulkifli; Sasmita, Rika Febri; Sari, Dina Mariana; Muryasari, Desiana; Caesare, ABD. (Jurnal Abdimas Bina Bangsa, 2024)
This extension programme was carried out at SMK NEGERI 7 Bandar Lampung with the aim of increasing students' understanding and awareness of plastic waste management into appropriate goods, as well as a discussion forum between students about the positive impact of good waste management on the environment and public health. This service has 2 discussion sessions, the first discussion focused on the leteration of waste sorting with the 3R method in everyday life, the second session on processing waste as a creative medium and how to turn waste into future savings. The next activity students are given the task to discuss in their groups. This forum is a forum for students to discuss, exchange ideas, and ask questions related to the material that has been presented. This discussion is also expected to strengthen students' understanding of the importance of waste management and literacy of waste classification using the 3R method in the context of everyday life. The activity ended with presentations by students containing the results of their discussions and conclusions. This presentation is a moment for students to show their understanding of waste management and classification. It is hoped that this programme can make a positive contribution in increasing students' awareness of the importance of waste management and waste classification literacy using the 3R method in everyday life.